Integration of tumour infiltrating lymphocytes, programmed cell-death ligand-1, CD8 and FOXP3 in prognostic models for triple-negative breast cancer: Analysis of 244 stage I–III patients treated with standard therapy. (September 2020) - Dieci, Maria Vittoria; Tsvetkova, Vassilena; Griguolo, Gaia; Miglietta, Federica; Tasca, Giulia; Giorgi, Carlo Alberto; Cumerlato, Enrico; Massa, Davide; Lo Mele, Marcello; Orvieto, Enrico; Guarneri, Valentina; Conte, Pierfranco
Abstract: Background: Tumour infiltrating lymphocytes (TILs) are an established prognostic biomarker for triple-negative breast cancer (TNBC). We evaluated the role of programmed cell-death ligand-1 (PD-L1), CD8 and FOXP3 expression in refining a prognostic model for non-metastatic TNBC beyond classic factors and TILs. Methods: Primary tumour samples from 244 early patients with TNBC, all treated with surgery and chemotherapy, were collected. Stromal TILs were evaluated on haematoxylin–eosin slides according to guidelines. PD-L1, CD8 and FOXP3 were assessed by immunohistochemistry and evaluated by digital pathology. Results: TILs, PD-L1, CD8 and FOXP3 were positively correlated with each other ( P  < 0.001). TILs were confirmed as an independent prognostic factor. When PD-L1, CD8 and FOXP3 were added to multivariable models including classic factors (age, stage, histologic grade) and TILs, PD-L1 provided the largest amount of additional prognostic information: likelihood ratio χ 2 4.60, P  = 0.032 (in a model including classic factors and TILs 10% increments) and likelihood ratio χ 2 6.50, P  = 0.011 (in a model including classic factors and TILs >30% versus <30%). In the subset of patients treated with neoadjuvant chemotherapy, FOXP3 provided further prognostic information beyond classic factors, TILs and pathological complete response (pCR) (likelihood ratio χ 2 5.01, P  = 0.025). For patients who did not achieve a pCR, the expression of CD8 and PD-L1 was significantly increased from baseline to residual disease. Conclusions: Beyond clinicopathological factors and TILs, other immune biomarkers may add prognostic information for early TNBC. The increased PD-L1 expression on residual disease after neoadjuvant chemotherapy strengthens the rationale of testing immune checkpoint inhibitors in the post-neoadjuvant setting. Highlights: Markers of immune activation are strongly prognostic in triple-negative breast cancer (TNBC). Our results support the recommendation that tumour infiltrating lymphocytes (TILs) should be evaluated in TNBC. Programmed cell-death ligand-1 (PD-L1) added significant prognostic information beyond classic factors and TILs. PD-L1 expression is significantly increased on residual disease after neoadjuvant chemotherapy.